Eco-friendly approach to enhance the mechanical performance of geopolymer foams: Using glass fibre waste coming from wind blade production. (10th April 2020) - Senff, L.; Novais, R.M.; Carvalheiras, J.; Labrincha, J.A.
Highlights: Aluminum powder and glass fibre waste used in the production of geopolymer mortar. DoE shows the influence of the GF and AP on lightweight geopolymer mortars. GF assure additional benefits in bridging the thin layers between adjacent pores. AP plays a dominant role on the physical and mechanical properties of mortars. GF improve the mechanical performance without affecting the insulation characteristic. Abstract: In this study, the possibility of using glass fibre wastes as reinforcement agent of waste-based and low thermal conductivity geopolymer mortars was evaluated to expand on previous work performed on dense geopolymers. The individual and combined influence of the glass fibre and the blowing agent amount on the fresh- and hardened-state properties of geopolymeric mortars was investigated. Results demonstrate that the fibres incorporation effectively enhances the mortars' flexural (up to 23%) and compressive strength (up to 30%) in comparison with the un-reinforced foams. Moreover, the fibres inclusion did not significantly alter the specimens' thermal conductivity, which demonstrates the suitability of the proposed approach. The low thermal conductivity (227 mW/m K) and apparent density (1.00 g/cm 3 ) of the mortars' associated with their flexural (1.23 MPa) and compressive strength (2.94 MPa) suggests the use of these innovative materials in non-structural applications.